Rejestr intercyz w aspekcie polskim i międzynarodowym - Pietrzak, Helena (Ius Matrimoniale, 2010)
The issue of marital property contracts is extremely interesting because of desiderata of „open and general availability of the register” appearing lately, which could affect certainty of civil law transactions, simplify taking up credits or accelerate court proceedings. In stipulators’ opinion, the obligatory register of marriage settlements would be only beneficial and result in effective limitation of present responsibility of spouses for failure to inform on any existence martial regime of separation of property. Experts stress that introduction of the obligatory register of marriage settlements to the Polish legal system [through a corresponding amendment to the Law on the National Court Register) or creation of such register from scratch, could enable any third person to obtain a confirmation of a legal and actual status of marital property relations, which consequently would facilitate and effectuate a fact of concluding a transaction. Because of a really wide spectrum of influence, and especially a practice in the European countries pointed to by the stipulators, in which such registers, in a facultative as well as an obligatory form, function – it is deemed appropriate to refer to the practice of its application, especially that for a long time some countries (e.g. Germany) have been explicitly requesting for dissolution of the register, pointing to statistics showing an obvious reduction and even lack of any interest by parties of such transactions.